Efficient Reconstruction of CAS-CI-Type Wave Functions for a DMRG State Using Quantum Information Theory and a Genetic Algorithm - Luo, Zhen; Ma, Yingjin; Liu, Chungen; Ma, Haibo (Journal of chemical theory and computation, 2017)
We improve the methodology to construct a complete active space-configuration interaction (CAS-CI) expansion for density-matrix renormalization group (DMRG) wave functions using a matrix-product state representation, inspired by the sampling-reconstructed CAS [SR-CAS; Boguslawski, K. ; J. Chem. Phys. 2011, 134, 224101 ] algorithm. In our scheme, the genetic algorithm, in which the “crossover” and “mutation” processes can be optimized based on quantum information theory, is employed when reconstructing a CAS-CI-type wave function in the Hilbert space. Analysis of results for ground and excited state wave functions of conjugated molecules, transition metal compounds, and a lanthanide complex illustrate that our scheme is very efficient for searching the most important CI expansions in large active spaces.